Enhancing the clinical utility of the Burn Specific Health Scale-Brief: Not just for major burns - Finlay, V.; Phillips, M.; Wood, F.; Hendrie, Delia; Allison, Garry; Edgar, D. (Pergamon, 2014)
Introduction: Like many other Western burn services, the proportion of major to minor burns managed at Royal Perth Hospital (RPH) is in the order of 1:10. The Burn Specific Health Scale-Brief (BSHS-B) is an established measure of recovery after major burns, however its performance and validity in a population with a high volume of minor burns is uncertain. Utilizing the tool across burns of all sizes would be useful in service wide clinical practice.Aim: This study was designed to examine the reliability and validity of the BSHS-B across a sample of mostly minor burn patients.Method: BSHS-B scores of patients, obtained between January 2006 and February 2013 and stored on a secure hospital database were collated and analysed Cronbach’s alpha, factor analysis, logistic regression and longitudinal regression were used to examine reliability and validity of the BSHS-B.Results: Data from 927 burn patients (2031 surveys) with a mean % total burn surface area (TBSA) of 6.7 (SD 10.0) were available for analysis. The BSHS-B demonstrated excellent reliability with a Cronbach’s alpha of 0.95. First and second order factor analyses reduced the40 item scale to four domains: Work; Affect and Relations; Physical Function; Skin Involvement, as per the established construct. TBSA, length of stay and burn surgery all predicted burn specific health in the first three months of injury (p < 0.001, p < 0.001, p = 0.03). BSHS-B whole scale and domain scores showed significant improvement over 24 months from burn (p < 0.001).Discussion: The results from this study show that the structure and performance of the BSHS-B in a burn population consisting of 90% minor burns is consistent with that demonstrated in major burns.Conclusion: The BSHS-B can be employed to track and predict recovery after burns of all sizesto assist the provision of targeted burn care.